ESTUDIO PRELIMINAR DE DISPERSIÓN DE SEMILLAS POR MICOS CHURUCOS (LAGOTHRIX LAGOTRICHA) EN EL PARQUE NACIONAL TINIGUA, COLOMBIA (2013)
An intensive study ofseed dispersa! by woolly monkeys (Lagothrit /agotriclza) was made at Tinigua National Park, Colombia. The feeding time in different fruit species recorded o ver focal animals. The number of seeds of each species found in depositions and the spatiallocation of feces was also noted. Results show that woolly monkeys play a majar role in seed dispersa!, because they defecate intact seeds of most of the fruit species consumed. Further indications. that woolly monkeys act as efficient dispersa! agents are their prolonged retention time through the digestive tract, their extensive use of the home range, the large number of depositions with one or two seeds per species and the fact that dispersed seeds are capable to germinate.